HUKUM PENGUPAHAN UNDANG-UNDANG CIPTA KERJA (UUCK) DAN KEINGINAN SEMUA PIHAK DALAM HUBUNGAN INDUSTRIAL - Ahmad Hunaeni Zulkarnaen (Universitas Suryakancana, 2020)
There must be harmony between the awareness and political attitude of the government that views the UUCK wage law can realize the wishes of all parties in industrial relations (Employers, Workers / Labor, Government), namely the desire of employer groups to realize productivity and/or corporate profit, the desire of workers/labor groups in the form of decent income and the desire of the government to improve the investment ecosystem and competitiveness of Indonesia. Therefore, the government must take and/or recommend a decision, strategically to realize the UUCK wage law that can simultaneously realize the wishes of all parties in industrial relations.Keywords : UUCK Wage Law, Industrial Relations, Employers, Workers/Labor.Â